Fluency and positivity as possible causes of the truth effect - Unkelbach, Christian; Bayer, Myriam; Alves, Hans; Koch, Alex; Stahl, Christoph (Consciousness and cognition, 2011)
Statements’ rated truth increases when people encounter them repeatedly. Processing fluency is a central variable to explain this truth effect. However, people experience processing fluency positively, and these positive experiences might cause the truth effect. Three studies investigated positivity and fluency influences on the truth effect. Study 1 found correlations between elicited positive feelings and rated truth. Study 2 replicated the repetition-based truth effect, but positivity did not influence the effect. Study 3 conveyed positive and negative correlations between positivity and truth in a learning phase. We again replicated the truth effect, but positivity only influenced judgments for easy statements in the learning phase. Thus, across three studies, we found positivity effects on rated truth, but not on the repetition-based truth effect: We conclude that positivity does not explain the standard truth effect, but the role of positive experiences for truth judgments deserves further investigation.
Erstmals am 12. Oktober 2010 veröffentlicht
Gesehen am 30.11.2022